Improved gradient iterative algorithms for solving Lyapunov matrix equations - 顾传青 范伟薇 (Journal of Shanghai University, 2008)
In this paper, an improved gradient iterative （GI） algorithm for solving the Lyapunov matrix equations is studied. Convergence of the improved method for any initial value is proved with some conditions. Compared with the GI algorithm, the improved algorithm reduces computational cost and storage. Finally, the algorithm is tested with GI several numerical examples.